2005
DOI: 10.1002/ana.20514
|View full text |Cite
|
Sign up to set email alerts
|

A PD‐1 polymorphism is associated with disease progression in multiple sclerosis

Abstract: T cells are considered to play a pivotal role in orchestrating the self-reactive immune responses in multiple sclerosis (MS). Programmed death 1 (PD-1) is a member of the B7/CD28 superfamily of costimulatory molecules exerting inhibitory functions on T cells. Recently, an intronic 7146G/A polymorphism within the PD-1 gene was described and suggested to be associated with autoimmunity. We investigated whether this genetic polymorphism is a genetic modifier for risk and progression of MS. Blood samples from 939 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
155
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(159 citation statements)
references
References 39 publications
2
155
1
1
Order By: Relevance
“…PD-1 has been shown to be important for selftolerance because spontaneous autoimmune diseases develop in PD-1 −/− mice (2)(3)(4). A single-nucleotide polymorphism that affects PD-1 expression is associated with autoimmune diseases in humans, such as systemic lupus erythematosus (5), type I diabetes (6), rheumatoid arthritis (7), and multiple sclerosis (MS) (8), suggesting that PD-1 deficiency may be a genetic factor involved in the development of autoimmunity.…”
mentioning
confidence: 99%
“…PD-1 has been shown to be important for selftolerance because spontaneous autoimmune diseases develop in PD-1 −/− mice (2)(3)(4). A single-nucleotide polymorphism that affects PD-1 expression is associated with autoimmune diseases in humans, such as systemic lupus erythematosus (5), type I diabetes (6), rheumatoid arthritis (7), and multiple sclerosis (MS) (8), suggesting that PD-1 deficiency may be a genetic factor involved in the development of autoimmunity.…”
mentioning
confidence: 99%
“…Following this line, such changes in expression levels of immune-regulatory molecules or adhesion molecules with their consequences with regard to T-cell invasion into the CNS might also account for so far unexplained decreases in the individual treatment response during the course of therapy, as observed in the context of natalizumab treatment. In this context, it is important to note that the B7-H1/PD-1 pathway is obviously key to susceptibility and disease type/course of several autoimmune disorders, including MS (41)(42)(43), which puts our findings into the overriding context of what functional consequences certain risk genes can have. This study demonstrates that single immune regulatory molecules affecting the activation status of (encephalitogenic) T cells can influence lesion distribution, which is associated with an altered capacity of these cells to elicit transient focal EC dysfunction and barrier dysfunction as essential steps for lesion development.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover PD 1.3 SNP has been reported in different autoimmune settings, including rheumatoid arthritis [14], Type I diabetes [11], Multiple sclerosis [15], Ankylosing spondylitis [16] and Allergy [17].…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 30 SNPs have been identified in human PD-1 gene [10,11]. Prokunina et al reported that the allele A of a SNP named PD1.3 (PD1.3A) in intron 4 is associated with the development of SLE in Europeans (relative risk=2.6) and Mexicans (relative risk=3.5) [12] To date, Single Nucleotide Polymorphism association with PD 1.3 has been reported in several auto-antibody associated autoimmune diseases; including psoriasis [13], rheumatoid arthritis [14], Type I diabetes [11], Multiple sclerosis [15], Ankylosing spondylitis [16] and Allergy [17].…”
Section: Introductionmentioning
confidence: 99%